Bacterial Communities Associated With Healthy and Diseased (Skeletal Growth Anomaly) Reef Coral Acropora cytherea From Palk Bay, India - Rajasabapathy, Raju; Ramasamy, Kesava Priyan; Manikandan, Balakrishnan; Mohandass, Chellandi; Arthur James, Rathinam (Frontiers in Marine Science, 2020)
Skeletal growth anomalies (SGA) are easily recognizable disease in reef-forming corals which drain energy from the host and end up with mortality. We collected mucus samples of healthy and SGA affected colonies of Acropora cytherea from Palk Bay, the southeast coast of India and investigated the taxonomic composition of mucus-associated bacterial communities using full-length 16S rRNA gene nanopore sequencing. Metagenomic analysis revealed the dominance of Proteobacteria, Firmicutes and Actinobacteria in both healthy and diseased samples. The proportion of Proteobacteria in diseased samples was almost doubled compared to the healthy one, whereas Acidobacteria (fourth dominant phyla in healthy sample) and Actinobacteria were significantly low in diseased samples. Planctomycetes, Cyanobacteria and Chloroflexi were some of the other major phyla found in healthy samples which were low in diseased corals. Kruskal-Wallis test indicated high number of putative pathogenic bacteria group viz. Staphylococcus, Salmonella, Klebsiella and Escherichia in diseased samples compared to healthy coral. The corals perhaps have acquired potential pathogens belong to the phylum Proteobacteria during SGA formation.